Characterization of antimicrobial, antioxidant, anticancer properties and chemical composition of Sauropus androgynus stem extract - WEI, Lee Seong; WEE, Wendy; YONG FU SIONG, Julius; SYAMSUMIR, Desy Fitrya (Acta medica Lituanica, 2011)
Background. This study describes antimicrobial, anticancer and antioxidant properties of Sauropus androgynus stem extract. The main objective of the present study was to reveal the potential of S. androgynus strip to be used as a medicinal drug. Materials and methods. The antimicrobial properties of S. androgynus stem extract against Aeromonas hydrophila, Escherichia coli, Edwardsiella tarda, Flavobacterium sp., Klebsiella sp., Salmonella sp., Vibrio alginolyticus, V. parahaemolyticus, V. cholerae and Pseudomonas aeruginosa were revealed by using the broth micro-dilution method, whereas the anticancer effects of the extract was determined with a colorimetric MTT (tetrazolium) assay against human breast adenocarcinoma (MCF-7). The antioxidant activity of the plant extract was characterized also by using a α, α-diphenyl-β-picrylhydrazyl (DPPH) radical scavenging method. Finally, chemical compounds of the plant extract were screened and identified by using gas chromatography – mass spectrometry (GC–MS). Results. The minimum inhibitory concentration (MIC) values ranged from 7.81 to 62.5 mg/l in which the plant extract was found to inhibit the growth of Edwardsiella tarda, Escherichia coli, Flavobacterium sp., Pseudomonas aeruginosa and Vibrio cholerae at 7.81 mg/l, Klebsiella sp., Aeromonas hydrophila and Vibrio alginolyticus at 15.6 mg/l, and it was able to control the growth of Salmonella sp. and Vibrio parahaemolyticus at 62.5 mg/l. The results of the present study has shown S. androgynus stem extract to possess a high antimicrobial activity and a moderate antioxidant activity (inhibition concentration 50%; IC50 of DPPH is 8 ppt), but no anticancer activity. A total of 34 compounds were identified in the plant extract in which the major compounds were 9, 12, 15-octadecatrienoic acid, methyl ester, (Z, Z, Z)- (14.48%) and phytol (13.08%). Conclusions. S. androgynus stem extract can be used as an antimicrobial and antioxidant agents. Keywords: antimicrobial, antioxidant, anticancer, chemical compound, Sauropus androgynus stem